2007
DOI: 10.1111/j.1741-3737.2006.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonstandard Schedules and Young Children’s Behavioral Outcomes Among Working Low‐Income Families

Abstract: This article focuses on how maternal employment in nonstandard schedules at night, on the weekends, or that rotate on a weekly basis influence preschoolers’ behavioral outcomes. Examining low‐income working mothers and their children aged 2 – 4 years from the Welfare, Children, and Families: A Three‐City Study (N= 206), we find that maternal nonstandard schedules are associated with negative behavioral outcomes for young children. There is some evidence that the negative effects of nonstandard schedules on beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(119 citation statements)
references
References 37 publications
4
110
2
2
Order By: Relevance
“…It has shown that the shorter the working hours of the mother, the higher the parenting stress score of the mother. Interestingly, this is contradicted with the study of [7] found the long hours would contribute negative impact for the parenting stress. The main reason might due to the culture of Chinese people that they prefer putting more effort in working rather than taking care of their child.…”
Section: B Inferential Data Analysis and Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…It has shown that the shorter the working hours of the mother, the higher the parenting stress score of the mother. Interestingly, this is contradicted with the study of [7] found the long hours would contribute negative impact for the parenting stress. The main reason might due to the culture of Chinese people that they prefer putting more effort in working rather than taking care of their child.…”
Section: B Inferential Data Analysis and Resultscontrasting
confidence: 53%
“…Thus, the result showed moderate significant relationship between mother's daily working hours and parenting stress. The present study was not coherent with some of the studies with indicated long working hours will create negative implication for the parenting stress [7]. The outcome of the current study is the shorter the working hours of a mother, the more parenting stress a mother intend to gain.…”
Section: To Determine Thecontrasting
confidence: 49%
“…The next set of analyses examined associations between mothers' work outside the home early in life and children's behavior problems combined over all times at which employment was assessed. In this second meta-analysis, we included 45 studies that compared behavior problem outcomes of children with employed mothers and nonemployed mothers (one study was excluded because it did not present a contrast for employment vs. no employment; Joshi & Bogen, 2007). For all behavioral outcomes combined, the average effect size estimated from all of the studies was very small and not significant (see Table 3).…”
Section: Behavior Problem Outcomesmentioning
confidence: 99%
“…In an analysis of Canadian data, Strazdins, Clements, Korda, Broom and D'Souza (2006) found that children whose parents worked nonstandard hours exhibited poorer emotional well-being, including higher incidence of anxiety and lower levels of self-control. These relationships appear particularly strong in low-income families, where children with mothers who work nonstandard hours exhibit significantly more behavioral problems and fewer positive behaviors in both single-mother and two-parent families (Joshi & Bogen, 2007).…”
Section: Influence Of Work Schedules On Parental Time With Childrenmentioning
confidence: 99%
“…Thus, the growth of nonstandard schedules, which are more common among single mothers, may affect them and their children in a particularly negative manner as compared to families dual-earner couples who have more options for allocating parental time. Further, when we consider that African-American, female, and low-wage workers comprise a disproportionately high number of individuals working non-standard schedules, these working arrangements may be further consolidating what are already remarkably durable forms of inequality (Presser, 2003b;Joshi & Bogen, 2007).…”
Section: Influence Of Work Schedules On Parental Time With Childrenmentioning
confidence: 99%